The Influence of Artificial Intelligence Technology Utilization and Personnel’s Knowledge and Competency in AI Applications on Work Performance in Local Administrative Organizations: A Case Study of Maha Sarakham Province - Worapongpat, Ntapat (Nakhon Ratchasima Journal of Humanities and Social Sciences, 2025)
This research aimed to (1) examine the influence of Artificial Intelligence (AI) technology utilization on personnel’s knowledge and competency in AI applications within local administrative organizations in Maha Sarakham Province, (2) investigate the effect of professional competence onpersonnel’s knowledge and competency in AI applications, and (3) analyze thecombined influence of AI technology utilization and professional competence on the work performance of local administrative personnel. A quantitative research design was employed using an online questionnaire distributed to 365 personnel from various local administrative organizations in Maha Sarakham Province. Data were analyzed using descriptive statistics—frequency,percentage, mean, and standard deviation—and inferential statistics through Multiple Regression Analysis (MRA).The results indicated that AI technology utilization had a significant positive effect on personnel’s knowledge and competency in AI applications (β = 0.19, p < 0.01), while professional competence also showed a significant effect (β = 0.21, p < 0.01). Furthermore, the combined influence of AI technology utilization and professional competence demonstrated a statistically significant positive impact on overall work performance (β = 0.45, p < 0.001). These findings highlight the importance of integrating AI adoption with personnel competency development to enhance organizational efficiency and service delivery within local administrative organizations.